Undermining local democracy : parallel governance in contemporary South India - Chandrashekhar, Lalita (New Delhi Routledge, 2011)
Based on the papers presented and discussions held at a high level Regional Forum organized by the Asian Development Bank in January 2010.
Includes bibliographical references and index